Effectiveness of an electronic apex locator used after preflaring of cervical and middle third - João Marcelo da Silva Teixeira; Myrna Bastos Barcellos; Marco André de Berrêdo Pinho; Carlos Augusto de Melo Barbosa; Rivail Antônio Sérgio Fidel; Sandra Rivera Fidel (Revista Sul-Brasileira de Odontologia, 2013)
The electronic method has been studied and improved aiming to add precision, speed and reliability of the measurement technique to determine the exact location of the working length. Currently, the root canal preparation recommends prior to determine the tooth length and consequent perform instrumentation of the apical portion, a previous preflaring of the cervical and middle thirds in various techniques. This procedure may provide a reduction in system impedance, leading to read errors by the apex locators. Objective: Investigate the influence of preflaring of the cervical and middle thirds on the accuracy of measuring the working length by apex locators. Material and methods: Twenty-five mesial roots of molars were used and had their crowns cut at the cemento-enamel junction. The actual measure of each root canal was performed and then the samples were embedded into a mixture of alginate, used as a conducting medium, where electronic measurements were taken with apex locator before and after preflaring of the canals with Gates-Glidden drills in descending order (#4, #3, #2). Measurements obtained by electronic method were then compared with the actual measurement of the root canal. The results were tabulated and submitted to the Student t test Results: The results show that there was no statistical significance (p<0.05) between the readings before and after preflaring. Readings closer to the foraminal ending occurred in the group after preflaring with Gates Glidden. Conclusion: It was concluded that preflaring with Gates Glidden drills were not able to influence significantly the accuracy of apex locator in determining the exact working length.